2023
DOI: 10.1371/journal.pone.0285740
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the cochlear and retrocochlear parts of the auditory system in 19–39 and 40–60 years old patients with type 1 diabetes mellitus

Abstract: Pathophysiological alterations in the cochlea and functional tests of the auditory pathway support that in diabetes both vasculopathy and neural changes could be present. The aim of our research was to study the differential effect of type 1 diabetes mellitus (T1DM) on two different age groups. Audiological investigation was carried out in 42 patients and 25 controls at the same age groups. Investigation of the conductive and sensorineural part of the hearing system by pure tone audiometry, distortion product … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…However, this was not statistically significant (p = 0.4538). This demonstrates that T1D may damage the hearing system, and this effect may increase with age [81].…”
Section: Plos Onementioning
confidence: 84%
See 4 more Smart Citations
“…However, this was not statistically significant (p = 0.4538). This demonstrates that T1D may damage the hearing system, and this effect may increase with age [81].…”
Section: Plos Onementioning
confidence: 84%
“…The two studies found there was a significant difference between PTAs [80,81], but one found there was no significant difference [83]. Additionally, one study found there was a significant difference in thresholds between the groups [81], but another study did not [82]. However, results showed that PTAs and OAEs were significantly worse in older diabetic individuals compared to younger subjects, indicating an association with age [81].…”
Section: Adultsmentioning
confidence: 95%
See 3 more Smart Citations